A Comparative of Life Cycle Assessment of a Conventional Van and a Battery Electric Van for an Online Shopping System in Thailand - J Koiwanit; C Hamontree (My University, 2018)
The transportation sector is responsible for one of the main emitters of large quantities of pollutions to the atmosphere, which impacts local, regional or global environment receptors. In Thailand, many retail chains have been trying to launch many campaigns and projects to reduce GHG emissions together with offering the best convenience services to serve customers' needs. By promoting an online shopping system for the workplace, this will mitigate even more of the air pollutants than the conventional online shopping system, where the products are delivered to customer's doorsteps. This study aims to investigate and compare the impact of different vehicle technologies for an online shopping using Life Cycle Assessment (LCA) methodology especially in the vehicle use phase. The observed results showed that the electric van has the potential of reducing emissions and consequently showed lower impacts in most impact categories.
Keywords: Electric Vehicles and Infrastructure